The First Decade of Colloidal Lead Halide Perovskite Quantum Dots (in our Laboratory) - Dmitry N. Dirin; Maksym V. Kovalenko (CHIMIA)
Ten years after the discovery of colloidal lead halide perovskite nanocrystals (LHP NCs), the field has witnessed substantial progress in synthetic methods, understanding of their surface chemistry and unique optical properties, precise control over NC size, shape, and composition. Ligand engineering, particularly with cationic and zwitterionic head groups, massively enhanced NC stability, compatibility with organic solvents, and photoluminescence efficiency. These breakthroughs allowed for the self-assembly of monodisperse NCs into complex long-range ordered superlattices and enabled the exploration of collective optical phenomena, such as superfluorescence. The development of low-cost scalable approaches like microfluidic systems and mechanochemical synthesis paved the way for the commercialization of LHP NCs, particularly for the down-conversion films in blue-backlit LCDs and as thermally-efficient color converters in pixelated displays. This review aims to trace the journey of these advancements, focusing on contributions from Switzerland, and outline future directions in this rapidly evolving field, such as quantum light sources, photocatalysis, etc.